Robust highly conductive patterns in flexible PEEK materials with either sp3 or sp2 dominant carbon phases produced by using ultrashort laser pulses - Ayesha Sharif; Nazar Farid; Yuhan Liu; Mingqing Wang; Robert G. Palgrave; Gerard M O'Connor (Applied Surface Science Advances)
This study reports ultrashort direct laser writing of highly conductive patterns on 50 µm thick flexible polyether-ether-ketone (PEEK) using two distinctive, electrically conductive regimes confirmed by XPS; an sp3-carbon dominant regime with minor sp2 contribution (Phase-I) and an sp2-carbon dominant regime with a small sp3 contribution (Phase-II). Phase-I is produced using a single laser scan strategy with a narrow fluence window. Phase-II is optimally produced using four sequential laser scan passes, each with a specific fluence. The rationale for the first pass was to disrupt carbon atoms, the second and third exposures were to gently modify this disrupted phase, and the fourth pass was to anneal the final structure. No characteristic graphene peaks were observed in Raman spectra for Phase-I, however, this phase surprisingly showed higher conductivity when compared with Phase-II. Raman peaks for graphene were observed for single laser scan passes at higher laser fluences with the onset of surface damage. In Phase-II, PEEK was laser scanned multiple times to transform into sp2 graphene integrated in the form of laser induced periodic surface structures. The lowest sheet resistance obtained was 9.60 Ω/□ and 11.53 Ω/□ corresponding to an electrical conductivity of ∼4.33 × 103 S/m and 4.17 × 103 S/m for Phase-I and Phase-II, respectively. The reported low-fluence process is significant for direct laser writing of conductive structures on polymers providing a precise and controlled manipulation of carbon configuration to produce components which are not impacted by mechanical friction.